Variants APOA5 p.G185C and p.S19W associated with early-onset severe hypertriglyceridemia-induced pancreatitis and diabetes complications in a Vietnamese girl - Hong Thu, Nguyen Huu; Thuy Linh, Nong; Huyen Thuong, Ma Thi; Thuy Duong, Nguyen; Hai Ha, Nguyen (Vietnam Journal of Biotechnology, 2023)
An imbalance of glucose and severely high triglyceride are the key characteristics driving hypertriglyceridemia and hyperlipidemic pancreatitis. Hereditary factors considerably promote the increase of triglyceride levels and secondary complications. This study explored the clinical characteristics and genetic causes of a young girl with recurrent severe hypertriglyceridemia-developed pancreatitis at 9-year-olds and diabetes mellitus appearance at 14-year-olds. At 20 years old, she was admitted to the hospital in critical condition and had pancreatitis pain with triglyceride level at 26.22 mmol/L, HbA1c 15%, and glucose at 21.3 mmol/L. Whole exome sequencing analysis showed that she had two heterozygous variants of the APOA5 gene, (p.G185C and p.S19W), one homozygous variant of the APOE gene (p.C156R), which were previously reported to cause critical hypertriglyceridemia condition of patients. The results and analysis propose these variations were the underlying causes of a heightened of patient's plasma triglycerides and lead metabolic complication onset at a young age. These findings shed light on the molecular mechanism of her elevated plasma triglyceride and the early onset of diabetes following hyperlipidemic pancreatitis.